Vacation Behaviour: Frequency, Destination Choice and Expenditure Level. - Ruben Van Loon; Jan Rouwendal; Piet Rietveld (European Regional Science Association (ERSA), 2010)
For many countries, tourism has a large impact on GNP, and the number of people employed in the tourist or related industries is large. We explain the decision whether to go on vacation on not and how often, the choice of destination and the decision on the level of expenditure, using different micro-econometric models. From these estimations we calculate for example the income elasticities. We use the CVO (2008) cross-section dataset of Dutch households. On average a Dutch holidaymaker spends ,Ç 24.68 a day for a domestic vacation and ,Ç 60.62 per day for a foreign vacation. Further, we discuss relevant characteristics of the vacations like type and duration of the vacation, the valuation of the vacation and destination. And we will discuss the characteristics of the households such as its composition and location.
Keywords: 330